Performance Management Implementation in Local Government: Lessons from Recent International Literature - Prashina Mohangi; Nyika, Farai (Universitas Medan Area, 2023)
There is an increased focus on employee performance management by employers, as a tool of improving efficiency of resource allocation and usage in local governments around the world. In an era of instant communication and widely available information, communities demand quality service delivery and they are quick to show their frustrations if their expectations are not met. Performance management has also been shown to increase local government accountability and transparency. The purpose of this article was to review and analyze relevant recent international academic literature to uncover themes and lessons in performance management implementation. A document review, was conducted to determine which studies to include in the literature survey by identifying (1) those published in an English peer reviewed journals on Google Scholar, and (2) those focused on performance management (PM) from an international/global perspective. The literature was classified into themes. In addition to classifying the articles, the paper summarizes the major findings of literature. This study finds that there are many challenges experienced in the implementation of performance management and there tends to be a mismatch of expectations of what performance management means to employees and employers. Also, Politicians dominate the administrative/ bureaucratic arm of local government, frustrating the purpose of performance management. This article also provides recommendations on how to improve the nature of performance management implementation.